Marsupials (Didelphidae, Mammalia) of Mato Grosso do Sul state (Brazil): taxonomic accounts, species richness, and biogeography - Cáceres, Nilton C. (2025)
The marsupials of Mato Grosso do Sul (MS) state in southwestern Brazil are still poorlyknown, with most research being concentrated around the Pantanal wetland. In thiswork, the marsupial richness was analysed in four different ecoregions of MS, based onmore than ten years of sampling using live and pitfall traps, comparing them with pub-lished information. Fifteen marsupial species were recorded, adding 117 new recordsand increasing the previously known richness by more than 50%. These new records rep-resent an increase between 96.7% (Gracilinanus agilis) to 9.1% (Chironectes minimus)of those previously known for the state, with an average increase of 43%. Cryptonanusagricolai is recorded for the first time for MS, but we did not trap Caluromys lanatus andMetachirus myosuros, which were mentioned in the literature. The Cerrado ecoregion (atype of savanna) shows more species than other ecoregions, being the largest ecore-gion in the state. A strong faunal turnover was found in the state, from the humid andmild forests of the southeast (Atlantic forest ecoregion) to the more seasonal, dry, andwarm forests, shrublands, and grasslands of the northwest (Chiquitano and Pantanalecoregions). A full taxonomic account and localities of the species recorded are pro-vided and the biogeographical affinities of ecoregions present in MS are discussed.